The Impact of Structural Transformation in the Retail Sector on the Producer and Consumer Market in Bursa - Seckin, Ebru (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2015)
There has been transformation of the food retail sector in the last 20 years, accompanied by multi-nationalization of the supermarket sector itself. Modern supply chains comprise the production and trade of high-value produce, usually destined for export to high-income markets or for supermarket retail. Two striking changes in the retail food sector have been the movement of supermarket chains towards specialized wholesalers in the organization of their procurement systems, and the emergence of strict quality and safety standards. Debates on the supermarket revolution and its impact on small farmers continue in the literature. Some writers suggest that small farmers are excluded from modern supply chains because they cannot meet supermarkets' requirements. However, some writers imply that small farmers are not under threat. In this context, this paper aimed to examine the relationship between buyer and supplier, and reveal the structural and behavioural stresses of the modern supply chain in the context of the pear supply chain in Bursa (Gursu). There are two research questions: 1) Are small farmers excluded from modern supply chains? 2) Are there differences between farmers in modern and traditional supply chains? The study concluded that there is a dual structure at work, in which traditional and modern supply chains intertwine and operate side by side. The study also found that small farmers are not excluded from the modern supply chain, and that there are no differences between farmers in modern and traditional supply chains.
Keywords: Bursa; rural development; supermarket; supply chain; producer market; AFRICA; GOVERNANCE; CHAINS; Architecture